Siema, zadanie na jutro :D

a) -(3-2x+4y²-2x³) + (-x³ - 2x² -2x-6)=
b)(n-7) - (2m+3m-4) - (4m-5n-7)=
c)(2a²-4ab-b²) - (a²-2ab-3ab²) + (8ab - 6b²)=
d)3-x²-(2-2x²-(3x²-2x+1))=
e)3x²-5x-(1-3x-(2+4x-x²))=
f)3x²-((xy-y²-2x)-(2x²+2xy-2x))=

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-25T15:40:48+01:00
A)-3+2x-4y²+2x³-x³-2x²-2x-6=-9-4y²+x³
b)n-7-2m-3m+4-4m+5n+7=6n-9m+4
c)2a²-4ab-b²-a²+2ab+3ab²+8ab - 6b²=3a²+a²+6ab-7b²
d)3-x²-2+2x²-3x²+2x-1=-2x²+2x-2
e)3x²-5x-1+3x-2-4x+x²=4x²-4x-3
f)3x²-xy+y²+2x-2x²-2xy+2x=x²+y²-3xy+4x
  • Użytkownik Zadane
2010-03-25T15:49:21+01:00
A)-(3-2x+4y²-2x³) + (-x³ - 2x² -2x-6)= -3 + 2x - 4y^ + 2x` - x` - 2x^ - 2x - 6 = -2x^+x`-9
b)(n-7) - (2m+3m-4) - (4m-5n-7) = n - 7 - 2m - 3m + 4 - 4m + 5n + 7 = 6n - 9m + 4
c)(2a²-4ab-b²) - (a²-2ab-3ab²) + (8ab - 6b²)=2a^ - 4ab - b^ - a^ + 2ab + 3ab^ + 8ab - 6b^ = a^ + 6ab + 3ab^ - 7b^
d) 3-x²-(2-2x²-(3x²-2x+1))=3-x^-(2-2x^-3x^+2x-1)= 3-x^-2-2x^+3x^-2x+1= -2x +2
e)3x²-5x-(1-3x-(2+4x-x²))= 3x^-5x-(1-3x-2-4x+x^)= 3x^-5x-1+3x+2+4x-x^= 2x^+2x+1
f)3x²-((xy-y²-2x)-(2x²+2xy-2x))= 3x^-(xy-y^-2x-2x^-2xy+2x)= 3x^ -xy+y^+2x+2x^+2xy-2x= 5x^+xy+y^


^ - do potęgi drugiej
` - do potęgi trzeciej